Consumer Rights and its Effects on Civil Law in Front to Hiring a Consumption Market - Durand Carrión, Julio Baltazar (2015)
The is now known as Human Rights and which are claimed as a right inherent in the human condition were not always designed in the same way, have followed a long evolutionary process. In this paper we examine the historical evolution from real concessions, through declarations (local or national) until its inclusion in the constitutional texts.